Impact of Climate Change on Land and Water Management: The Case of Nepal, India and Bangladesh - Shrestha, Krishna Kumar; Timsina, Tatwa P. (Journal of Advanced Academic Research, 2017)
Agriculture is the backbone of economic development of country like Nepal, India and Bangladesh. Quantity and quality of production depends on quality of soils, irrigation facilities, quality of seeds, farming methods and time, climate, quality and types of fertilizer and the technologies used. In the recent times, the climate change has been reported to impact highly in the performance of the agriculture sector of these countries. Because of the rise of temperature, there is much concern on food securities and other agricultural issues like the changes in cropping pattern due to changing rainfall pattern thus impacting directly and indirectly to their gross domestic product. The objective of this study was to assess the situations against the climate change perspectives including the soil and water issues and its impacts on agriculture and food security of these communities. It also aimed to examine the local adaptation cases with respect to developing criteria for potential adaptation possibilities at the local community level and to make a comparative study in three locations of South Asia namely Madhuri village, Rupandehi district (foot hills) of Nepal, Vaishali village, Patna State (plains) of India and Harikahali village, Khulna district (sea coast) of Bangladesh. The finding of this study helps to provide policy support in mainstreaming adaptation at the community level in the context of natural resource management for the vulnerable communities of the three locations of SA region, and helps governments, development partners and donors in their planning and implementation of climate change related activities from a long term regional perspectives.